Silver Diamine Fluoride in Restorative Dentistry: An Effective Approach in Root Caries - pervez, Jazib; Saleem, Suffiyan; Ghani, Bushra; Ahmed, Farrukh; Ishaq, Bismah; Iqbal, Humara (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the effectiveness of Silver Diamine Fluoride (SDF) as a conservative treatment for root caries, offering an alternative to more invasive restorative procedures.Study Design: Randomized Controlled Trial (ACTRN: 0000386513).Place and Duration of Study: Bakhtawar Amin Dental College, Multan, Pakistan, from Mar-Aug 2023.Methodology: The study enrolled 90 patients with caries lesions and assigned them to two groups: Group A received 38% SDF, and Group B received 5% NaF sodium fluoride varnish. Follow-up assessments were conducted at one month, evaluating caries arrest through clinical examinations.Results: The SDF group demonstrated a higher efficacy in caries arrest (78.12%) compared to NaF varnish (35.29%). Visual inspection, lesion size measurement, and texture assessment were crucial in determining the success of SDF application. Statistical analysis revealed a significant difference between the groups, having p-value of .000459, supporting the superior efficacy of SDF.Conclusion: Our study found that the 38% SDF is a better treatment option for root caries compared to NaF varnish, providing long-lasting effects.